Developing a framework for utilizing adjunct rehabilitation therapies in motor recovery of upper extremity post stroke. Issue 5 (4th July 2023) - Teasell, Robert; McIntyre, Amanda; Viana, Ricardo; Bateman, Emma A.; Murie-Fernandez, Manuel; Janzen, Shannon; Saikaley, Marcus
ABSTRACT: Introduction: Standardization of first principles has transformed stroke rehabilitation in developed countries and helped guide the appropriate allocation of resources to ensure better outcomes for patients. There have been challenges in incorporating new evidence into stroke rehabilitation practices. The sheer number of RCTs can be daunting to the average clinician, made worse by the lack of a framework for their application. Objectives: To develop a framework for the introduction of adjunct practices for the motor recovery of the upper extremity post stroke into clinical practice. Methodology: A literature search following PRISMA guidelines revealed 1, 307 RCTs involving rehabilitation interventions for the hemiparetic upper extremity post stroke. Results: Therapies were divided into three categories of therapies: (1) Basic Conventional Therapy Approaches (<15% of interventions), (2) Adjunct Therapies Designed to Enhance Conventional Therapies (>85% of interventions), and (3) Treatment to Manage Complications (~9% of interventions). Adjunct Therapies, despite having a spectacular evidence base, are often not employed clinically. To encourage their clinical use, we have developed a framework that divides adjunct therapies into two categories: (1) Treatments that Stimulate the Brain (i.e. rTMS, mental practice, and virtual reality) and (2) Treatments that Peripherally Facilitate the Hemiparetic Upper Extremity (i.e. robotics, EMG Biofeedback, and Constraint-induced Movement Therapy). Conclusion: To allow stroke rehabilitation to continue to improve upper extremity recovery and outcomes, we propose a new intuitive framework that is based on a strong evidence base to guide clinicians and improve stroke rehabilitation.